2023
DOI: 10.3390/vaccines11050996
|View full text |Cite
|
Sign up to set email alerts
|

Association between Overweight/Obesity and the Safety and Efficacy of COVID-19 Vaccination: A Systematic Review

Abstract: Objective: The objective of this study was to appraise the interrelation between overweight/obesity and the safety and efficacy of COVID-19 vaccination by synthesizing the currently available evidence. Methods: A systematic review of published studies on the safety and efficacy of the COVID-19 vaccine in people who were overweight or obese was conducted. Databases including Embase, Medline Epub (Ovid), PsychInfo (Ovid), Web of Science, PubMed, CINAHL, and Google Scholar were searched to identify relevant studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…However, more than half of the overweight (55.17%, n = 240) and 75% (n = 6) of the severely obese vaccinated individuals reported one to three AEs after the second dose (p = 0.03). Our finding is parallel to the controversy observed in the literature, as indicated in a very recent systematic review published in May 2023, which aimed to assess the safety and efficacy of COVID-19 vaccines specifically in individuals who were overweight or obese [28]. Among the included studies, 13 reported the use of BNT162b2 (Pfizer-BioNTech, USA), while four studies reported the use of ChAdOx-nCov19 (AstraZeneca, UK).…”
Section: Discussionsupporting
confidence: 74%
“…However, more than half of the overweight (55.17%, n = 240) and 75% (n = 6) of the severely obese vaccinated individuals reported one to three AEs after the second dose (p = 0.03). Our finding is parallel to the controversy observed in the literature, as indicated in a very recent systematic review published in May 2023, which aimed to assess the safety and efficacy of COVID-19 vaccines specifically in individuals who were overweight or obese [28]. Among the included studies, 13 reported the use of BNT162b2 (Pfizer-BioNTech, USA), while four studies reported the use of ChAdOx-nCov19 (AstraZeneca, UK).…”
Section: Discussionsupporting
confidence: 74%
“… 74 , 79 Encouraging healthy eating habits, physical activity, and weight reduction should be emphasized. 80 The low rate of reinfection among vaccinated individuals in our study indicates that immunity produced by vaccination remains effective despite the ongoing mutation of the COVID-19 virus and the emergence of new VOCs. While there is controversy, one meta-analysis reported that certain variants (Beta, Gamma and Delta) may have the ability to evade immunity induced by vaccination.…”
Section: Discussionmentioning
confidence: 57%
“…However, this supports findings from other studies suggesting a potential association ( 67 , 68 ). The literature emphasizes the current lack of conclusive evidence regarding vaccine safety in the obese population ( 69 ). Further research is necessary to delve into the mechanisms underlying this potential association.…”
Section: Discussionmentioning
confidence: 99%